Chemical exposures in recently renovated low-income housing: Influence of building materials and occupant activities. (December 2017) - Dodson, Robin E.; Udesky, Julia O.; Colton, Meryl D.; McCauley, Martha; Camann, David E.; Yau, Alice Y.; Adamkiewicz, Gary; Rudel, Ruthann A.
Abstract: Health disparities in low-income communities may be linked to residential exposures to chemicals infiltrating from the outdoors and characteristics of and sources in the home. Indoor sources comprise those introduced by the occupant as well as releases from building materials. To examine the impact of renovation on indoor pollutants levels and to classify chemicals by predominant indoor sources, we collected indoor air and surface wipes from newly renovated "green" low-income housing units in Boston before and after occupancy. We targeted nearly 100 semivolatile organic compounds (SVOCs) and volatile organic compounds (VOCs), including phthalates, flame retardants, fragrance chemicals, pesticides, antimicrobials, petroleum chemicals, chlorinated solvents, and formaldehyde, as well as particulate matter. All homes had indoor air concentrations that exceeded available risk-based screening levels for at least one chemical. We categorized chemicals as primarily influenced by the occupant or as having building-related sources. While building-related chemicals observed in this study may be specific to the particular housing development, occupant-related findings might be generalizable to similar communities. Among 58 detected chemicals, we distinguished 25 as primarily occupant-related, including fragrance chemicals 6-acetyl-1, 1, 2, 4, 4, 7-hexamethyltetralin (AHTN) and 1, 3, 4, 6, 7, 8-hexahydro-4, 6, 6, 7, 8, 8-hexamethylcyclopenta[ g ]-2-benzopyran (HHCB). The pre- to post-occupancy patterns of the remaining chemicals suggested important contributions from building materials for some, including dibutyl phthalate and xylene, whereas others, such as diethyl phthalate and formaldehyde, appeared to have both building and occupant sources. Chemical classification by source informs multi-level exposure reduction strategies in low-income housing. Graphical abstract: Highlights: Pre- and post-occupancy measurements were used to classify sources of SVOCs and VOCs as building- or occupant-related. Primarily occupant-related chemicals included synthetic fragrance chemicals. DBP and xylene had important building-related sources whereas DEP and formaldehyde had both building and occupant sources. All homes had indoor air concentrations that exceeded available risk-based screening levels for at least one chemical. Chemical classification by source informs multi-level exposure reduction strategies in low-income housing.